Downregulation of TNFR2 decreases survival gene expression, promotes apoptosis and affects the cell cycle of gastric cancer cells - Rossi, Ana Flávia Teixeira [UNESP]; da Silva Manoel-Caetano, Fernanda [UNESP]; Biselli, Joice Matos [UNESP]; Cabral, Ágata Silva [UNESP]; de Freitas Calmon Saiki, Marilia [UNESP]; Silva, Ana Elizabete [UNESP]; Ribeiro, Marcelo Lima (Baishideng Publishing Group, 2022)
BACKGROUND Chronic inflammation due to Helicobacter pylori (H. pylori) infection promotes gastric carcinogenesis. Tumour necrosis factor-α (TNF-α), a key mediator of inflammation, induces cell survival or apoptosis by binding to two receptors (TNFR1 and TNFR2). TNFR1 can induce both survival and apoptosis, while TNFR2 results only in cell survival. The dysregulation of these processes may contribute to carcinogenesis. AIM To evaluate the effects of TNFR1 and TNFR2 downregulation in AGS cells treated with H. pylori extract on the TNF-α pathway. METHODS AGS cell lines containing TNFR1 and TNFR2 receptors downregulated by specific shRNAs and nonsilenced AGS cells were treated with H. pylori extract for 6 h. Subsequently, quantitative polymerase chain reaction with TaqMan® assays was used for the relative quantification of the mRNAs (TNFA, TNFR1, TNFR2, TRADD, TRAF2, CFLIP, NFKB1, NFKB2, CASP8, CASP3) and miRNAs (miR-19a, miR-34a, miR-103a, miR-130a, miR-181c) related to the TNF-α signalling pathway. Flow cytometry was employed for cell cycle analysis and apoptosis assays. RESULTS In nonsilenced AGS cells, H. pylori extract treatment increased the expression of genes involved in cell survival and inhibited both apoptosis (NFKB1, NFKB2 and CFLIP) and the TNFR1 receptor. TNFR1 downregulation significantly decreased the expression of the TRADD and CFLIP genes, although no change was observed in the cellular process or miRNA expression. In contrast, TNFR2 downregulation decreased the expression of the TRADD and TRAF2 genes, which are both important downstream mediators of the TNFR1- mediated pathway, as well as that of the NFKB1 and CFLIP genes, while upregulating the expression of miR-19a and miR-34a. Consequently, a reduction in the number of cells in the G0/G1 phase and an increase in the number of cells in the S phase were observed, as well as the promotion of early apoptosis. CONCLUSION Our findings mainly highlight the important role of TNFR2 in the TNF-α pathway in gastric cancer, indicating that silencing it can reduce the expression of survival and anti-apoptotic genes.
Keywords: Gastric cancer; Helicobacter pylori; miRNAs; TNFR1; TNFR2; Tumour necrosis factor-α signalling pathway